State Institutional Format in the Constitution of 1945 after Amendment: Political and Legal Perspectives - Am'mar Abdullah Arfan; Taufiqur Rohman (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
This research discusses the state institutional format in the Constitution of 1945 after the amendment. Since the Constitution 1945 had four changes from 1999 to 2022, so need to know what implications for all state institutions. The Constitution is the supreme law of the land in the Indonesian legal system, which was used as the basis for all social practice, nation, and state. This research used a normative approach in which the formation of the state is in accordance with its designation or not. The study of the content used normativejuridical or doctrinal methods. This study found that the third and fourth amendments to the 1945 Constitution established three new institutions, namely the DPD, the Constitutional Court (MK) and the Judicial Commission, while the Supreme Consultative Council was abolished. With amendments to the 1945 Constitution, the MPR is no longer the highest institution. Likewise, changes in the constitutional system. These changes cover the government system (the President and Vice President as one leading institution),the representative system (MPR consisting of the DPR and DPD), and the justice system (MA and MK). The reformed format for organizing state institutions in the 1945 Constitution applies a system of enhancing power and the principle of checks and balances between state institutions, as in democratic countries.